Maternal welfare (leaflet)
1933 1933 1930s 1 page MATERNAL WELFARE Under the Maternity and Child Welfare Act, 1918, a Local Authority has power to aid the Maternity Service of the district in the following ways :— (1) The appointment of Health Visitors, whose duties include attendance at an Ante-natal and Post-natal Centre, and the visiting of expectant mothers. (2) The establishment of Ante-natal Clinics for expectant mothers, and of Post-natal Clinics which mothers can attend immediately after confinement. (3) Assistance to Midwives (a) The provision of sterilised maternity outfits free or at cost price. (b) A subsidy to enable a midwife to practise in a district which would otherwise not support her. (c) The appointment, where necessary, of municipal midwives. (d) The payment of part fees to a midwife when the patient cannot afford the full fee. (e) "Refresher" courses for practising midwives. (4) Maternity Homes or beds in a Maternity Hospital for :— (a) Complicated cases. (b) Patients whose home circumstances are unsuitable for a confinement at home. (c) Ante-natal observation. (d) The treatment of puerperal sepsis. (5) Home Helps (6) The Provision of Milk or Food during the last three months of pregnancy and during lactation. (7) Complicated Midwifery (a) The fees of doctors called in by midwives for an "emergency" in connection with a confinement must be paid, if necessary, in whole or in part. (b) The fee of a consultant called in by a doctor for a complicated midwifery case or for puerperal infection. (c) Skilled nursing for patients confined at home. (d) Bacteriological examination in cases of puerperal infection. (8) Convalescent Home Treatment for mothers after confinement. (9) District Nursing Associations. Payments can be made for midwifery and maternity nursing, or for the nursing of puerperal fever. Assistance can also be given towards the establishment of new Nursing Associations in areas where a midwife is required. (10) Provision can also be made for assisting unmarried mothers and their children. NOTE : Patients are expected to contribute towards the cost of special services according to their means. Further information can be obtained from the Ministry of Health Reports and Circulars. Printed by the LONDON CALEDONIAN PRESS LTD, 74 Swinton Street, W.C.1. and published by THE MATERNAL MORTALITY COMMITTEE, 13, Chester Terrace. S.W.1 — W28791 292/824/1/41